Myopathies caused by homozygous titin mutations: limb-girdle muscular dystrophy 2J and variations of phenotype. Issue 11 (22nd June 2010) - Pénisson-Besnier, I; Hackman, P; Suominen, T; Sarparanta, J; Huovinen, S; Richard-Crémieux, I; Udd, B
Abstract : Limb-girdle muscular dystrophy 2J caused by mutations in C-terminal titin has so far been identified in Finnish patients only. This may in part be due to limited availability of diagnostic tests for titin defects. In this report, a French family with an autosomal-dominant late-onset distal myopathy of the tibial muscular dystrophy phenotype segregating in several members of the family was described. One deceased patient in the family proved to be homozygous for the C-terminal truncating titin mutation because of consanguinity. According to available medical records, the patient had a clearly more severe generalised muscle weakness and atrophy phenotype not recognised as a distal myopathy at the time. Autopsy findings in one of the original Finnish limb-girdle muscular dystrophy 2J patients were reported and the early phenotype in a newly identified young patient with homozygous Finnish C-terminal titin mutation (FINmaj) was detailed.